2017
DOI: 10.1177/0379572117723396
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Edible Palm Weevil Larvae (Akokono) as a Source of Nutrition and Livelihood: Perspectives From Ghanaian Stakeholders

Abstract: Anticipated barriers to scaling up akokono micro-farming include a need for greater familiarity with and acceptance of the insect as food for infants and young children and creation of a sustainable market. Engagement with stakeholders, including health workers, will facilitate use of akokono as a complementary food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…Most of the species of palm weevil have already been studied. Among the various species, the following had been profiled: African palm weevil R. phoenicis in Cameroon (Fogang Mba et al 2017;Womeni et al 2009Womeni et al , 2012, Nigeria (Adeyeye 2017;Edijala et al 2009;Ekpo and Onigbinde 2005;Elemo et al 2011;Ogbuagu et al 2011;Okunowo et al 2017;Omotoso and Adedire 2007) and Ghana (Atuahene et al 2017;Laar et al 2017); R. palmarum in Côte d'Ivoire (Dué et al 2009;Gbogouri et al 2013) and Nigeria (Adeyeye 2017), and R. ferrugineus in Egypt (Abdel-Moniem et al 2017) and Malaysia (Ali et al 2006). However, based on the review of available scientific literature, no nutritional information can be found for the species R. bilineatus.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the species of palm weevil have already been studied. Among the various species, the following had been profiled: African palm weevil R. phoenicis in Cameroon (Fogang Mba et al 2017;Womeni et al 2009Womeni et al , 2012, Nigeria (Adeyeye 2017;Edijala et al 2009;Ekpo and Onigbinde 2005;Elemo et al 2011;Ogbuagu et al 2011;Okunowo et al 2017;Omotoso and Adedire 2007) and Ghana (Atuahene et al 2017;Laar et al 2017); R. palmarum in Côte d'Ivoire (Dué et al 2009;Gbogouri et al 2013) and Nigeria (Adeyeye 2017), and R. ferrugineus in Egypt (Abdel-Moniem et al 2017) and Malaysia (Ali et al 2006). However, based on the review of available scientific literature, no nutritional information can be found for the species R. bilineatus.…”
Section: Introductionmentioning
confidence: 99%
“…Effects are worse in the populations that already have high rates of malnutrition, such as Zambia, where chronic undernutrition is 45% and causes 52% of deaths in the population under the age of 5. Over 800 million people are thought to have a food energy deficit average of >80 kcal/day/person [3,15].…”
Section: Food Insecuritymentioning
confidence: 99%
“…To prevent future undernutrition and to decrease current levels, food access and socioeconomic conditions must improve globally [14]. With this climate change-driven prediction of reduced agricultural yields in most countries given current crop practices and varieties, it is therefore necessary to increase the diversity and sustainability of crop supply so that food insecurity is not exacerbated [15].…”
Section: Food Insecuritymentioning
confidence: 99%
See 2 more Smart Citations